2013
DOI: 10.13080/z-a.2013.100.047
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate variability in Lithuania and Belarus on atmospheric precipitation infiltration: lysimetric study

Abstract: The average annual rate of atmospheric precipitation is about 38-40% on the territories of the Republics of Lithuania and Belarus. On agricultural land, with runoff waters various chemical elements leach into the subsoil and cause negative impact on the quality of water bodies. The main objectives of this study were to assess the influence of climate variability on the infiltration of atmospheric precipitation in Lithuania (Vilnius) and Belarus (Minsk). The long-term lysimetric experiment (lysimeter surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…The air temperature and precipitation change patterns in BiH are consistent with the predominant trends in other areas of East Europe (Branković et al, 2013;Bukantis & Rimkus, 2005a;Bukantis & Rimkus, 2005b;Burić et al, 2013;Jaagus et al, 2009;Rutgersson et al, 2014;Tripolskaja & Pirogovskaja, 2013;Unkasevic & Tosic, 2013) and with trends observed globally (Jacob et al, 2018;Kharin et al, 2013;Popov et al, 2018b;Trenberth et al, 2013).…”
Section: Resultssupporting
confidence: 83%
“…The air temperature and precipitation change patterns in BiH are consistent with the predominant trends in other areas of East Europe (Branković et al, 2013;Bukantis & Rimkus, 2005a;Bukantis & Rimkus, 2005b;Burić et al, 2013;Jaagus et al, 2009;Rutgersson et al, 2014;Tripolskaja & Pirogovskaja, 2013;Unkasevic & Tosic, 2013) and with trends observed globally (Jacob et al, 2018;Kharin et al, 2013;Popov et al, 2018b;Trenberth et al, 2013).…”
Section: Resultssupporting
confidence: 83%
“…The increasing trends of the air temperature (T) are similar for Kaunas and Sarajevo WS, ranging from 0.052 0 C to 0.047 0 C. Increasing trends ware also detected for the annual amount of precipitation, ranging from 3.582 mm year -1 in Kaunas to 1.724 mm year -1 in Sarajevo, Annual sum of precipitation has increased by more than 100 mm in Kaunas for a period of 30 years . The observed air temperature and precipitation change patterns in Lithuania and B&H are consistent with the predominant trends in other areas of East Europe Bukantis ArūNas & Rimkus Egidijus, 2005;Jaagus et al, 2009;Branković et al, 2013;Burić et al, 2013;Tripolskaja & Pirogovskaja, 2013;Unkasevic & Tosic, 2013;Rutgersson et al, 2014) and with trends observed globally (Kharin et al, 2013;Trenberth et al, 2013;Jacob et al, 2018;Popov et al, 2018).…”
Section: Resultssupporting
confidence: 84%
“…Degirmendžić et al [48] showed a downward trend in almost the entire country, which supports views that the continental features of pluvial conditions are weakening slightly. The situation is similar in many regions of Europe, e.g., in Germany [49] and Belarus [50].…”
Section: Discussionmentioning
confidence: 77%